Analysis of Coordination of Social Support Services during COVID-19 Pandemic in New Zealand - Takeda, Mariko (The Journal of The Japan Society for New Zealand Studies, 2024)
This paper aims to analyze the coordination role of providing social support services to individuals and families with hardship under COVID-19 pandemic in New Zealand; where strict lockdowns were implemented in the early stages of the COVID-19 epidemic. Three analysis were made; the characteristics and changes in the social security and social welfare system before 2020, measures and methods of providing social support services during the pandemic, and the function of coordination and connecting services based on the needs of individuals and families provided by various social service providers. The third analysis was conducted through interview survey of Coordinators of Heartland Services and Community Connection Services providers, and the Manager for Community Connection Service of Ministry of Social Development.